Consumer Buying Behaviour in Two-wheeler Industry-with Special Reference to Hero Honda Motorbikes - Kameswari, M. L.; Santosh Kumari, A.; Raghunatha Reddy, D. (Indian Journal of Marketing, 2005)
Industrialization has brought vast changes in the Automobile Industry, because growth and development of any area requires appropriate transportation facilities. Automobile industry is one of the fastest growing sectors in our country. The rapid growth of middle class section is the primary reason for the growth of two-wheeler Industry. People in rural and semi urban areas are trying to elevate their life style and people in metropolitan cities are completely disappointed with the public transport system. India is the third largest manufacturer and second largest consumer of two wheelers in the world. It has been achieved due to variety of reasons like restrictive policy of the Government of India and rising demand for personal transport.